Art Therapy in Australian Prisons: A Research Agenda - Tucker, Sarah (International journal of offender therapy and comparative criminology, 2025)
Art therapy in prisons remains widely under-researched in Australia and beyond and represents a major gap in the literature. Despite evidence that art therapy can be a tool for social change, to date, there are no recorded studies in Australia which have investigated the therapeutic benefits of art in prison populations with measured outcomes. Literary analysis suggests that research tends to be hampered by limitations in methodological approaches that are suited to prison environments. By engaging “inside” with inmates over the course of an 8-week art therapy program, this research design addresses this knowledge gap. Building on 5 years of piloting, the research methodological design presented in this paper embodies a prototype that promises to overcome the limitations of previous research approaches. This research agenda promises to facilitate creative interventions through sensitively attuned art therapy delivery. Benefits are expected to accrue to diverse stakeholder groups, including inmates, chaplaincy and parole services, voluntary facilitators, policymakers, criminologists, and taxpayers, among others.